Pengaruh Struktur Modal, Likuiditas, dan Pertumbuhan Penjualan terhadap Nilai Perusahaan dengan Profitabilitas sebagai Variabel Mediasi Studi pada Perusahaan yang Terdaftar di BEI Periode 2019 – 2024 - Anggraini, Diana Indah Sri Lestari Pratiwi; Hwihanus, Hwihanus (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
The food and beverage industry listed on the Indonesia Stock Exchange (IDX) between 2019 and 2024 is the subject of this study, which empirically investigates the link between capital structure, liquidity, sales growth, and business value. Using structural equation modeling (SEM) through SmartPLS 4, this study finds empirical evidence that capital structure significantly influences firm liquidity. However, it was discovered that company value was not significantly impacted by capital structure, liquidity, sales growth, or profitability. These results imply that company value in the food and beverage industry may be more heavily influenced by variables beyond the purview of this investigation.